Risk Score for Predicting In-Hospital Mortality in COVID-19 (RIM Score) - López Escobar, Alejandro; Madurga, Rodrigo; Castellano, José María; Velázquez, Sara; Suárez del Villar, Rafael; Menéndez, Justo; Peixoto, Alejandro; Jimeno, Sara; Ventura Wichner, Paula Sol; Ruiz de Aguiar, Santiago (My University, 2024)
Infection by SARS-CoV2 has devastating consequences on health care systems. It is a global health priority to identify patients at risk of fatal outcomes. 1955 patients admitted to HM-Hospitales from 1 March to 10 June 2020 due to COVID-19, were were divided into two groups, 1310 belonged to the training cohort and 645 to validation cohort. Four different models were generated to predict in-hospital mortality. Following variables were included: age, sex, oxygen saturation, level of C-reactive-protein, neutrophil-to-platelet-ratio (NPR), neutrophil-to-lymphocyte-ratio (NLR) and the rate of changes of both hemogram ratios (VNLR and VNPR) during the first week after admission. The accuracy of the models in predicting in-hospital mortality were evaluated using the area under the receiver-operator-characteristic curve (AUC). AUC for models including NLR and NPR performed similarly in both cohorts: NLR 0.873 (95% CI: 0.849¿0.898), NPR 0.875 (95% CI: 0.851¿0.899) in training cohort and NLR 0.856 (95% CI: 0.818¿0.895), NPR 0.863 (95% CI: 0.826¿0.901) in validation cohort. AUC was 0.885 (95% CI: 0.885¿0.919) for VNLR and 0.891 (95% CI: 0.861¿0.922) for VNPR in the validation cohort. According to our results, models are useful in predicting in-hospital mortality risk due to COVID-19. The RIM Score proposed is a simple, widely available tool that can help identify patients at risk of fatal outcomes. Keywords: COVID-19; neutrophil-to-platelet ratio; NPR; neutrophil-to-lymphocyte ratio; NLR; hemogram-derived-ratios
Keywords: COVID-19; neutrophil-to-platelet ratio; NPR; neutrophil-to-lymphocyte ratio; NLR; hemogram-derived-ratios